Effects of degree of milling and kernel fragment size on the moisture desorption behavior of Pinilisa Rice at 27C - Lendero, Edeul Paul C. author
This study focused on the effects of degree of milling and fragment size on the moisture desorption behavior of Pinilisa rice at 27°C. Static gravimetric method using modified proximity equilibration cell was used to determine the equilibrium moisture contents (EMC) of Pinilisa rice samples with different degrees of milling (paddy, dehulled, undermilled, and regular milled) and fragment sizes (whole, broken, ground) at various levels of relative humidity (RH). The EMCs of the Pinilisa rice samples generally decreased with decreasing RH. Significant differences (p<0.05) in EMC and hygroscopic equilibration time were observed in all Pinilisa rice samples across all RH levels. Type II isotherms typical to food including rice were observed in all samples. Modified Halsey model had the best fit (RSS=0.9-20; r2=95-99; MRD=0.06-0.08) in most samples while Modified Henderson model had the poorest fit. The inflection points in the desorption isotherms differed across samples. The first inflection point ranged from 9.10% to 14.91% RH, while the second inflection point ranged from 72.79% to 83.72% RH. The monolayer values obtained using the BET and GAB models, as well as the first inflection point differed, but the GAB monolayer values and those approximated using the first inflection point were closer. Results showed that the moisture desorption behavior of Pinilisa rice at 27°C varies across degrees of milling and fragment sizes. This implies that different drying conditions are required for each form of Pinilisa rice. Furthermore, inconsistent trends in the equilibration time of different fragment sizes at various RH levels mean that grinding Pinilisa rice samples does not necessarily shorten their hygroscopic equilibration time at 27°C.